Social skills in institutionalized teenagers: A group play intervention - Estrada Rodríguez , Rosa Cindy (Consorcio de Universidades Mexicanas A.C., 2016)
Social skills are involved in many areas of a person’s life, improving aspects such as the adaptation to their living environment and their health protection, both physical and mental. The increase of social skills in institutionalized teenagers may be particularly beneficial, because of the risk situations of the environment they come from, and that can be causes of other problems in young people. This paper, a case study, seeks to promote the use of social skills in this population through a ludic group workshop. The results show that this kind of intervention result in the increase of social skills, since an increase was observed in the skills of seven of the eight members.